(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
With urbanization and growth of cities, there is need andurgency for better governance. Urban governance is no more limited to provisionof infrastructure and operation of civic services. Conventional methods of governancewith top-down approaches are considered inadequate, inappropriate andrestrictive. Good urban governance is characterized by sustainability, equityand efficiency, transparency and accountability, civic engagement, securitydevelopment of partnerships etc. liability, competitiveness and bank abilityare the other features of a modern city There is a need for prudent andefficient financial and asset management to increase their capacity tofacilitate market borrowing for investment in city development. Keeping theseemerging challenges of 21" century, the Government of India launchedJawaharlal Nehru National Urban Renewal Mission with three interrelated andcomplimentary components - governance, infrastructure development and provisionof basic services to poor, implementation of governance reforms like enactmentor community participation and public disclosure laws, earmarking of funds forpoverty alleviation by local bodies, levy and collection of user charges,simplification of procedures etc.